Review of advanced emergency evacuation procedures in hospital buildings: comprehensive analysis and insights - Wu, Hao; Nie, Ruimin; Zeng, Xu; Cheng, Chuanjie; Pan, Jing; Han, Daguang; Hosamo, Haidar (Frontiers in Built Environment, 2024)
This research paper explores the integration of novel technologies in hospital emergency evacuations, particularly in Operating Rooms (ORs) and Emergency Departments (EDs). It examines the application of advanced tools like simulation modeling, Building Information Modeling (BIM), Digital Twin technology, sensor data, and AI to improve evacuation strategies in the building. The study extends to in-depth case studies for assessing the practicality of existing protocols, while also highlighting the critical importance of staff training and preparedness. Additionally, it addresses the ethical and psychological impacts of emergencies on patients and healthcare staff, underscoring the need for technology to be complemented with human-centered care. The paper concludes by emphasizing the ongoing necessity for innovative research in enhancing safety and operational resilience in healthcare emergency management.